Análise da deformabilidade do fosfogesso - Chagas, Juliana Verônica Ribeiro das (2014)
The phosphogypsum, a by-product from the production of phosphoric acid, requires the availability of large areas for its storage, representing a problem for the industries of fertilizers, both economically and environmentally. Therefore, there is a need to search for alternative applications of phosphogypsum in order to minimize the impacts of its deposition. Several studies were performed to verify the possibility of using phosphogypsum in geotechnical works, which showed promising results. However, the deformability of this material can be a limiting factor for their use. Thus, one of the main objectives of this study was to analyse the evolution of deformation over time of the phosphogypsum, soil and a mixture containing 10% of phosphogypsum and 90% of soil (mixture A). Furthermore, this study also analysed the deformability of these materials when they are not saturated, which is the natural condition in which they are used. The phosphogypsum was collected in a phosphate fertilizers industry, called Anglo American, in the city of Catalão, Goiás, and the soil was collected in Aparecida de Goiânia, Goiás. For the analysis of deformation over time, consolidation tests were performed with different loading times (48 hours, 7 days and 15 days) on samples in saturated condition. After the consolidation tests, others tests were conducted in order to give a better understanding of the results, such as: X-Ray diffraction, permeability, scanning electron microscopy (SEM) and tests to obtain the water retention curve using the equipment WP4C (Dewpoint PotentiaMeter). For the analysis of the deformation in unsaturated condition, consolidation tests in unsaturated conditions and tests of water content control were performed in the soil, phosphogypsum and mixture A (10% phosphogypsum + 90% soil). The results show no stabilizing of the deformation over time of the mixture A and the phosphogypsum. Furthermore, the increase of the deformation due only to the secondary compression expected for a period of five years is approximately 0.5% for the soil, 1.4% for the mixture A and 15.5% for the phosphogypsum. It has been found by granulometry tests that the deformations occur due to the breakage of the grains of phosphogypsum. It is noteworthy that no mineralogical change occurs, as observed by X-ray diffraction. Furthermore, it was verified with the unsaturated consolidation tests that a slight variation of suction occurs during the test, but this variation influenced more the deformability of the phosphogypsum than of the soil and mixture A. Thus, it was concluded that the deformation limits the use of phosphogypsum or mixtures of phosphogypsum and soil in geotechnical works.